The Effect of Hemodialysis Treatment on Quality of Life and Sleep in Patients with Chronic Kidney Disease - Demir, Mustafa; Canpolat, Omer; Demir, Fadime; Cicek, Sedat; Dogukan, Ayhan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2019)
Objective: This study aimed to compare quality of life and sleep between patients with hemodialysis and patients with stage 3-4 chronic kidney disease (CKD) who did not receive hemodialysis treatment. Material and Methods: A total of 139 patients (56 female and 83 male) diagnosed with CKD who were being followed up at our clinic were included. Of these, 101 were dialysis patients (dialysis CKD group), and 38 were non-dialysis patients (non-dialysis CKD group). Patients were asked to complete the sociodemographic questionnaire, 36-Item Short Form Health Survey, and Pittsburgh Sleep Quality Index. The chi-square test, Fisher exact test, t-test, and Mann-Whitney test were used to assess differences between the groups according to test assumptions. Results: In terms of gender, age, height, education, exercise, and smoking, no statistically significant differences (p> 0.05) were observed between the groups. Weight was found to be significantly higher in the nondialysis group than in the dialysis CKD group (p=0.001). Quality of life scores were compared; statistically significant differences were found in terms of general health (p=0.003), mental health (p=0.001), and fitness (p=0.008) subscales. Three parameters were higher in the dialysis patients' hemodialysis group. Sleep quality subscales were compared; sleep disturbance (p=0.007) and sleeping pill use (p=0.014) were statistically significant. Sleep disturbance and sleeping pill use they were higher in the nondialysis group. Conclusion: Our study results suggest that impairment of quality of life and sleep is because of chronic kidney disease and not because of hemodialysis. Furthermore, hemodialysis treatment improves some subparameters of life and sleep quality.
Keywords: Chronic kidney disease; hemodialysis; quality of life; quality of sleep